NF-κB/c-Rel DNA-binding is reduced in substantia nigra and peripheral blood mononuclear cells of Parkinson's disease patients - Vanessa Porrini; Andrea Pilotto; Marika Vezzoli; Annamaria Lanzillotta; Michele M. Gennari; Sonia Bonacina; Antonella Alberici; Rosanna Turrone; Arianna Bellucci; Angelo Antonini; Alessandro Padovani; Marina Pizzi (Neurobiology of Disease, 2023)
Although Parkinson's disease (PD) key neuropathological hallmarks are well known, the underlying pathogenic mechanisms of the disease still need to be elucidated to identify innovative disease-modifying drugs and specific biomarkers. NF-κB transcription factors are involved in regulating several processes associated with neurodegeneration, such as neuroinflammation and cell death, that could be related to PD pathology. NF-κB/c-Rel deficient (c-rel−/−) mice develop a progressive PD-like phenotype. The c-rel−/− mice present both prodromal and motor symptoms as well as key neuropathological features, including nigrostriatal dopaminergic neurons degeneration, accumulation of pro-apoptotic NF-κB/RelA acetylated at the lysine 310 residue (Ac-RelA(lys310)) and progressive caudo-rostral brain deposition of alpha-synuclein. c-Rel inhibition can exacerbate MPTP-induced neurotoxicity in mice. These findings support the claim that misregulation of c-Rel protein may be implicated in PD pathophysiology. In this study, we aimed at evaluating c-Rel levels and DNA-binding activity in human brains and peripheral blood mononuclear cells (PBMCs) of sporadic PD patients. We analyzed c-Rel protein content and activity in frozen substantia nigra (SN) samples from post-mortem brains of 10 PD patients and 9 age-matched controls as well as in PBMCs from 72 PD patients and 40 age-matched controls. c-Rel DNA-binding was significantly lower and inversely correlated with Ac-RelA(lys310) content in post-mortem SN of sporadic PD cases, when compared to healthy controls. c-Rel DNA-binding activity was also reduced in PBMCs of followed-up PD subjects. The decrease of c-Rel activity in PBMCs from PD patients appeared to be independent from dopaminergic medication or disease progression, as it was evident even in early stage, drug-naïve patients. Remarkably, the levels of c-Rel protein were comparable in PD and control subjects, pointing out a putative role for post-translational modifications of the protein in c-Rel dysfunctions.These findings support that PD is characterized by the loss of NF-κB/c-Rel activity that potentially has a role in PD pathophysiology. Future studies will be aimed at addressing whether the reduction of c-Rel DNA-binding could constitute a novel biomarker for PD.